Blue-Light-Absorbing Thin Films Showing Ultralong Room-Temperature Phosphorescence - Louis, Marine; Thomas, Heidi; Haft, Anna; Fries, Felix; Reineke, Sebastian; Gmelch, Max (Advanced Materials, 2019)
The development of organic materials displaying ultralong room-temperature phosphorescence (URTP) is a material design-rich research field with growing interest recently, as the luminescence characteristics have started to become interesting for applications. However, the development of systems performing under aerated conditions remains a formidable challenge. Furthermore, in the vast majority of molecular examples, the respective absorption bands of the compounds are in the near ultraviolet (UV) range, which makes UV excitation sources necessary. Herein, the synthesis and detailed analysis of new luminescent organic metal-free materials displaying, in addition to conventional fluorescence, phosphorescence with lifetimes up to 700 ms and tailored redshifted absorption bands, allowing for deep blue excitation, are reported. For the most promising targets, their application is demonstrated in the form of organic programmable tags that have been recently developed. These tags make use of reversible activation and deactivation of the URTP by toggling between the presence and absence of molecular oxygen. In this case, the activation can be achieved with visible light excitation, which greatly increases the use case scenarios by making UV sources obsolete.
Keywords: biluminescence; organic programmable tags; persistent phosphorescence; room-temperature phosphorescence; visible light excitation